Foscarnet in the management of cytomegalovirus infections in hematopoietic stem cell transplant patients. Issue 11 (November 2012) - Bacigalupo, Andrea; Boyd, Alan; Slipper, Jackie; Curtis, Jim; Clissold, Steve
Despite significant advances in the day-to-day management of patients receiving hematopoietic stem cell transplantations, including the introduction of new antiviral drugs, cytomegalovirus (CMV) infection continues to be a major cause of morbidity and mortality. The aim of this article is to undertake a literature-based review of foscarnet in this therapeutic setting and to align current best-published evidence with recent recommendations presented at the European Conference on Infections in Leukaemia . Ganciclovir remains the mainstay of CMV infection/disease antiviral management protocols. However, approximately a third of patients develop severe neutropenia and others become resistant to ganciclovir, and thus, a reasonably large proportion of patients are not able to receive and/or continue with this medication. Foscarnet is a suitable option as both pre-emptive therapy or for the treatment of active disease in these patients. Randomized trials have demonstrated that foscarnet is equally effective when compared with ganciclovir for pre-emptive treatment of CMV infections: the outcome was comparable with ganciclovir in terms of control of antigenemia and survival rates. There is a paucity of information for its use in the prophylaxis of CMV, although preliminary data show that it was effective in some patients at high risk of CMV reactivation. The main adverse events associated with foscarnet are renal impairment, serum electrolyte and hemoglobin disturbances, seizures and local genital irritation/ulceration. Foscarnet is a well-established antiviral option in immunocompromised patients, and it is usually administered as a second-line option to ganciclovir. In patients receiving hematopoietic stem cell transplantation, it has proven efficacy when used pre-emptively to treat CMV reactivation, as an alternative to and also in combination with ganciclovir.